PERTUMBUHAN DAN HASIL TANAMAN CABAI DI LAHAN KERING YANG DITUMPANGSARIKAN DENGAN TANAMAN KACANG-KACANGAN PADA WAKTU TANAM YANG BERBEDA - Sari, Ulfa Kariska; Jaya, I Komang Damar; Nufus, Novita Hidayatun (AGROTEKSOS; Vol 33 No 1 (2023): Jurnal Agroteksos April 2023DO - 10.29303/agroteksos.v33i1.804, 2023)
This study aimed to determine growth and yield of red chili ( Capsicum annum L.) in dryland intercropped with legumes at different planting times. A field experiment was conducted from May to September 2022 in Amor-Amor Hamlet, Gumantar Village, Kayangan District, North Lombok Regency. There were six intercropping treatments and three monoculture treatments tested. The treatments were: intercropping chili with groundnut or with mungbean planted or inserted at the same time, one week and three weeks after planting (WAP) the chili. The monoculture treatments were chili, groundnut and mungbean. The treatments were arranged in a Randomized Block Design with three replications. The results showed that intercropping chili with mungbean and groundnut at various planting times affected the growth and yield of chili. The yield of chili increased with the presence of groundnut planted simultaneously and with mungbean planted three weeks after chili. Meanwhile, there was a decrease in the yield of groundnut and mungbean as a result of intercropping treatment.